Selling Australia. Tourist Town / Film Australia in association with Prospero Productions ; produced in association with the Australian Broadcasting Corporation ; directed by Julia Redwood ; produced by Ed Punchard and Julia Redwood ; written by Julia Redwood and Lawrie Silvestrin. - Thornton, Sigrid, 1969-; Redwood, Julie; Redwood, Julie; Redwood, Julie; Punchard, Ed (National Film and Sound Archive of Australia, 2000)
In tropical far-north Queensland, Cairns is a tourist mecca. As planeload after planeload of visitors arrive, even the customs officials are getting training in hospitality and cultural sensitivity. For tourists, the town seems pretty close to paradise, but it's not quite perfect. Cairns has no beach. No problem - Cairns City Council has decided to build one. However, as the heavy machinery moves in, some locals are up in arms. It seems that, for the sake of its biggest industry, Cairns will do virtually anything to please.